1984
DOI: 10.2105/ajph.74.10.1130
|View full text |Cite
|
Sign up to set email alerts
|

Polybrominated biphenyls and fetal mortality in Michigan.

Abstract: The contamination of the Michigan food supply by polybrominated biphenyls (PBBs) in the mid-1970s appears to have had little or no impact on fetal mortality. Comparison of fetal death rates among residents of Lower Peninsula counties with a high percentage of quarantined farms and among residents of Upper

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In humans, studies of women who were exposed to PBB when they were children or adults did not show a consistent association between exposure level and gestational age or birth weight of their infants (Humble and Speizer, 1984; Givens et al, 2007; Small et al, 2007). However, a study of in utero women who were exposed to PBB suggested that those with higher exposures during this critical window had increased odds of spontaneous abortion when they reached adulthood and became pregnant, compared to those with the lowest exposure (Small et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…In humans, studies of women who were exposed to PBB when they were children or adults did not show a consistent association between exposure level and gestational age or birth weight of their infants (Humble and Speizer, 1984; Givens et al, 2007; Small et al, 2007). However, a study of in utero women who were exposed to PBB suggested that those with higher exposures during this critical window had increased odds of spontaneous abortion when they reached adulthood and became pregnant, compared to those with the lowest exposure (Small et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…13,14 The effect of in utero exposure may differ from adult exposure on reproductive outcomes because the initiation of follicular development occurs in utero. Furthermore, the concentration of exposure relative to body weight is larger for a fetus compared to an adult.…”
mentioning
confidence: 99%
“…The associations observed here lend support to the hypothesis that pubertal events may be affected by pre-and postnatal exposure to organohalogens. Humble and Speizer (1984) carried out a study to evaluate fetal mortality (spontaneous abortions occurring after 20 weeks of gestation) in the Michigan cohort. The high exposure group consisted of seven lower peninsula counties with between 6.8 per cent and 20.4 per cent of total farms quarantined per county.…”
Section: Effects On Fertility or Offspringmentioning
confidence: 99%